Fuzzy Modeling and Genetic Algorithms for Data Mining and Exploration - Cox, Earl (The Morgan Kaufmann series in data management systems, 2005)
Fuzzy Modeling and Genetic Algorithms for Data Mining and Exploration is a handbook for analysts, engineers, and managers involved in developing data mining models in business and government. As you'll discover, fuzzy systems are extraordinarily valuable tools for representing and manipulating all kinds of data, and genetic algorithms and evolutionary programming techniques drawn from biology provide the most effective means for designing and tuning these systems.